Cyclic volatile methyl siloxanes (D4, D5, and D6) as the emerging pollutants in environment: environmental distribution, fate, and toxicological assessments - Kumari, Kanchan; Singh, Anshika; Marathe, Deepak (Environmental science and pollution research international, 2024)
Cyclic volatile methyl siloxanes (cVMS) have now become a subject of environmental contamination and risk assessment due to their widespread use and occurrence in different environmental matrices. Due to their exceptional physio-chemical properties, these compounds are diversely used for formulations of consumer products and others implying their continuous and significant release to environmental compartments. This has captured the major attention of the concerned communities on the grounds of potential health hazards to human and biota. The present study aims at comprehensively reviewing its occurrence in air, water, soil, sediments, sludge, dusts, biogas, biosolids, and biota and their environmental behavior as well. Concentrations of cVMS in indoor air and biosolids were higher; however, no significant concentrations were observed in water, soil, and sediments except for wastewaters. No threat to the aquatic organisms has been identified as their concentrations do not exceed the NOEC (maximum no observed effect concentration) thresholds. Mammalian (rodents) toxicity hazards were not very evident except for the occurrence of uterine tumors in very rare cases under long-term chronic and repeated dose exposures in laboratory conditions. Human relevancy to rodents were also not strongly enough established. Therefore, more careful examinations are required to develop stringent weight of evidences in scientific domain and ease the policy making with respect to their production and use so as to combat any environmental consequences. Graphical Abstract